Reactivation strategies for nucleation-inhibited catalyst beds in continuously operated gas-release reactions from liquids - Uhrig, Felix; Solymosi, Thomas; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (International Journal of Hydrogen Energy, 2023)
In reactions that release gaseous products from liquids, heterogeneous, porous catalysts can be in an active or nucleation-inhibited state as has recently been shown by our group for batch dehydrogenation reactions. This paper investigates this practically highly relevant phenomenon now in a continuous tube reactor for the example of liquid organic hydrogen carrier (LOHC) dehydrogenation. A mechanical stimulus, increase in reaction temperature or decrease in residence time reactivates the inhibited catalyst bed. Furthermore, the experimental results indicate that the dehydrogenation reaction turns into a hydrogenation reaction for thermodynamic reasons as the catalyst bed cools down. Hydrogenation is responsible for the consumption of the gas phase and thus a liquid filling of the pellets, which causes the nucleation-inhibition. Our work reveals new aspects of nucleation-inhibition on catalyst beds and provides insights into the efficient operation of heterogeneous catalytic gas release reactions in which this phenomenon occurs.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Dehydrogenation; LOHC; Nucleation-inhibited catalyst; Reactivation